Virtual Reality Pembelajaran Bahasa Jepang Berbasis Android - Tiwi Afriani Hasman; Tommy; Divi Handoko (SNASTIKOM, 2022)
The rapid development of technology makes information media now switch to virtual reality. Virtual reality is atechnology that allows users to interact with a computer simulated environment. The Japanese language itself hasa different accent and its own uniqueness. The advantages of this virtual reality technology will help Androidbasedsmartphoneuserstobeabletodevelopapplicationswithvirtualrealitytechnology,especiallyinlearning Japanese. With this application, it will overcome the time constraints in learning Japanese. This study aims toanalyze the application of virtual reality technology in learning Japanese. The results of the research conductedby the author is to produce a Japanese language learning media using virtual reality technology, especially inkatakana and hiragana letters. In addition, this application also features a quiz feature as a benchmark for users'understanding of learning Japanese, as well as a Japanese sentence feature that can train users to apply Japanesein daily activities. Based on the results of research and testing of 20 respondents with the results agreeing anaverage of 78%, doubting 18% and disagreeing 4%, it can be concluded that the resulting application still needsdevelopment on its features and the system that has been made to be more effective used by users, as well asadjustments to educational needs.